'Hip to be Irish': ethnicity and Bourdieu's 'Forms of Capital'. Issue 10 (8th August 2016) - Sullivan, Thomas
ABSTRACT: A 'new Irish' American ethnicity surfaced in the 1980s – according to a number of scholars and journalists – and is comprised of what some consider to be more 'authentic' and 'traditional' Irish cultural attributes. Defining authentic and traditional Irishness is complicated, however, by the recent influx and highly visible forms of economic capital and media attention stemming from the Celtic Tiger – the surge of economic prosperity that began in Ireland in the 1990s – and the commercializing of Irish music and dance – such as Riverdance . In this paper, I propose, through my study involving Irish language enthusiasts, that this 'new' form of Irish ethnicity is more the result of rather than the reason for this surge in popularity. I use Pierre Bourdieu's 'Forms of Capital' in questioning the 'new Irish' American ethnicity, arguing instead that a deeply seated, less-visible reservoir of cultural and social capital form the basis for this perceived contemporary ethnicity.